The Relationship Between Parenting Patterns and Students' Learning Independence - Barita Esman Dabukke, Asaaro Laia, Yetti Rosmawati Pangaribuan, Eka Saputri Sinaga (Education Achievement: Journal of Science and Research, 2021)
This research aimed to determine the relationship beetwen parenting parents with the learning independence students which is implemented at the SD Negeri 066652 Medan Helvetia in June academic 2022. This research used approachment that used a method of analysis correlation. The sample in this research is fourth grade students SD Negeri 066652 Medan Helvetia with the totaling 38 people. This research used data collection techniques in the form of a questionnaire and to test yhe hypothesis used product moment correlation analysis form Karl Pearson. The result of this research indicate that there is a positive relationship between parenting parents with the learning independence of class IV SD Negeri 066652 Medan Helvetia with most correlation 12,1%.